(untitled) (Journal of Forensic Medicine & Toxicology, 2011)
A retrospective study was carried out on 160 suicide cases autopsied at the Forensic Medicine Center in Dammam, Kingdom of Saudi Arabia (from 2003 to 2007). Of these cases, 131 (81.87%) were males and 29 (18.13%) were females, and the ratio of the males to females was 4.5 : 1 Approximately two thirds (107 cases) from the studied subjects were in the third and fourth decades. The largest proportion of suicides was among Indian population (41.25%), followed by Saudi nationals (20.625%), and other fourteen different nationalities. Suicide by hanging was the most common method in the majority of cases (83.125%) followed by firearm self shooting in only 8 individuals (5%) and other seven methods of suicide. Multiple suicidal methods were used in just 9 cases. More than 80% of the cases were laborers and maids, the rest were jobless, housewives or related to other occupations. Family troubles were documented in 16 cases (10%) while a history of psychological illnesses was given in double this figure (31 cases). Suicidal notes were discovered in the scene of death in 5% of cases. Postmortem blood alcohol was revealed in only 5.625% of cases, and toxicological analysis resulted in detection of amphetamine and cannabinoids, in 2.5% and 1.875% of them, respectively. In conclusion, there was a outstandingly decrease in suicide rate in Dammam from 51 cases (2.55/100,000 population) in 2003 to 23 cases (1.15/100,000 population) in 2007.